Evaluating the Effectiveness of a 2D Mindfulness Meditation Animation in Enhancing Student Creativity in Batam City - Pratama, Jimmy; Fenky, Fenky; Wibowo, Tony (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to evaluate the effectiveness of a 2D mindfulness meditation animation in enhancing students’ creativity at higher education institutions in Batam City through perceived perception. This study is considered important since mindfulness activities have been widely recognized for improving one’s ability to concentrate, reduce stress, and foster creativity, yet limited studies have explored its integration through digital animation media. The research applied a descriptive qualitative approach using the MDLC model, which consists six phases: concept, design, material collecting, assembly, testing, and distribution. Data were gathered through open-ended interviews with 20 university students who watched the developed 2D animation, analyzed descriptively to explain participants’ perceptions and response. The results indicate that 65% of participants experienced better relaxation and focus, while 62% reported increased motivation for creative thinking after viewing the animation. The synchronized narration, soft pastel visuals, and calm pacing effectively supported mindfulness engagement, although the short duration limited deeper relaxation. The findings suggest that mindfulness-based animation can serve as an alternative learning medium to promote emotional balance and cognitive readiness. The novelty of this study lies in combining mindfulness practice and educational animation to enhance creativity among non-psychology students in Indonesia. These findings imply that the integration of mindfulness principles into interactive learning media can enrich educational innovation and mental well-being in higher education.